The Influence of Green Brand towards Green Personal Care Product Purchase Decision with Green Knowledge as Moderating Variable (A Study on â€œOriginal Sourceâ€ Consumers in Malang) - SE, Dwivanny Retnaningtyas (Jurnal Ilmiah Mahasiswa FEB, 2019)
Being one of the industries that highly impacts the environment, the Fast-Moving Consumer Goods (FMCG) industry, especially the personal-care category is a growing business in Indonesia. Many FMCG businesses have shifted their business into a greener and more sustainable one. Even so, the amount of waste stockpiled in Indonesia is still the second largest in the world. This shows the low decision to purchase green product by Indonesian consumer. This research aimed to identify whether if Green Brand perception in Original Source brand impact consumersâ€™ Green Product Purchase Decision and whether if Green Knowledge moderate the influence. The type of research is explanatory research with a quantitative approach. The data used was primary data in the form of a survey with a questionnaire as the data collection instrument. There are 150 respondents as the sample selected based on several criteria. The analysis method used is Multiple Regression Analysis (MRA) using the SPSS 23 software for Windows. The result of the research implies that Green Brand influence is positively significant to Green Product Purchase Decision. The second finding shows that Green Knowledge influence is able to moderate and weaken the relationship of Green Brand towards Green Product Purchase Decision.Keywords: Green Brand, Green Knowledge, Purchase Decision